MiR‐205 is up‐regulated in islets of diabetes‐susceptible mice and targets the diabetes gene Tcf7l2. (29th June 2021) - Ouni, Meriem; Gottmann, Pascal; Westholm, Efraim; Schwerbel, Kristin; Jähnert, Markus; Stadion, Mandy; Rittig, Kilian; Vogel, Heike; Schürmann, Annette
Abstract: Aim: MicroRNAs play an important role in the maintenance of cellular functions by fine‐tuning gene expression levels. The aim of the current study was to identify genetically caused changes in microRNA expression which associate with islet dysfunction in diabetic mice. Methods: To identify novel microRNAs involved in islet dysfunction, transcriptome and miRNome analyses were performed in islets of obese, diabetes‐susceptible NZO and diabetes‐resistant B6‐ ob/ob mice and results combined with quantitative trait loci (QTL) and functional in vitro analysis. Results: In islets of NZO and B6‐ ob/ob mice, 94 differentially expressed microRNAs were detected, of which 11 are located in diabetes QTL. Focusing on conserved microRNAs exhibiting the strongest expression difference and which have not been linked to islet function, miR‐205‐5p was selected for further analysis. According to transcriptome data and target prediction analyses, miR‐205‐5p affects genes involved in Wnt and calcium signalling as well as insulin secretion. Over‐expression of miR‐205‐5p in the insulinoma cell line INS‐1 increased insulin expression, left‐shifted the glucose‐dependence of insulin secretion and supressed the expression of the diabetes gene TCF7L2 . The interaction between miR‐205‐5p and TCF7L2 was confirmed by luciferase reporter assay. Conclusion: MiR‐205‐5p was identified as relevant microRNA involved in islet dysfunction by interacting with TCF7L2 .